COMMITMENT IN THE HEBREW BIBLE: MOSES, ELIJAH AND JEREMIAH - Frizzel, Lawrence E. (Journal of Dharma, 1987)
Religious commitment may be defined as "spiritual dedication on a. permanent basis to a way of life that demands above-average generosity and requires more than ordinary grace of God." I Although we do not expect to find such a term in ancient literature, there are indeed examples of the reality underlying the concept. From early times people set ideals for themselves and their followers by presenting models for imitation. Popular culture may extol an outlaw or noncomformist, but the mature community will treasure the person who sacrificed self-interest for service of others. The individual who grapples with a crisis and sets an example of strength in adversity will be celebrated in epic and ballad. Thus the biblical tradition celebrates Joel and Dehorah, Gideon and Samson. It also commemorates those who maintained a firm grip on the helm in fair weather as well as foul. Does the strength manifested in a moment of danger have its counterpart in virtue governing the decisions of daily life? Therein lies the test of profound commitment to spiritual ideals.